Ischemic stroke in children and young adults with sickle cell disease in the post‐STOP era. Issue 12 (1st November 2019) - Kwiatkowski, Janet L.; Voeks, Jenifer H.; Kanter, Julie; Fullerton, Heather J.; Debenham, Ellen; Brown, Lynette; Adams, Robert J.; ,
Abstract: The Stroke Prevention Trial in Sickle Cell Anemia (STOP) and Optimizing Primary Stroke Prevention in Sickle Cell Anemia (STOP 2) trials established routine transcranial Doppler ultrasound (TCD) screening, with indefinite chronic red cell transfusions (CRCT) for children with abnormal TCD as standard of care. Implementation failures and limitations to the STOP protocol may contribute to continued ischemic stroke occurrence. In the "Post‐STOP" study, we sought to assess the impact of the STOP protocol on the incidence of ischemic stroke in a multicenter cohort of former STOP and/or STOP 2 trial participants. A central team abstracted data for 2851 (74%) of the 3835 children who took part in STOP and/or STOP 2. Data included TCD and neuroimaging results, treatment, laboratory data, and detailed clinical information pertaining to the stroke. Two stroke neurologists independently confirmed each stroke using pre‐specified imaging and clinical criteria and came to consensus. Among the 2808 patients who were stroke‐free at the start of Post‐STOP with available follow‐up, the incidence of first ischemic stroke was 0.24 per 100 patient‐years (95% CI, 0.18, 0.31), with a mean (SD) duration of follow‐up of 9.1 (3.4) [median 10.3, range (0‐15.4)] years. Most (63%) strokes occurred in patients in whom the STOP protocol had not been properly implemented, either failure to screen appropriately with TCD (38%) or failure to transfuse adequately patients with abnormal TCD (25%). This study shows that substantial opportunities for ischemic stroke prevention remain by more complete implementation of the STOP Protocol.